2018
DOI: 10.1186/s12889-018-6130-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal grand multiparity and intention to use modern contraceptives in Nigeria

Abstract: BackgroundGrand multiparity and low contraceptive prevalence are dominant among Nigerian women. These elevate the risk of unintended pregnancies, high-risk fertility and adverse maternal and child health outcomes among women in the country, particularly grand multiparous women. Studies have examined predictors of intention to use modern contraceptives among women of reproductive age. However, these studies did not ascertain the extent to which grand multiparity is associated with intention to use modern contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 63 publications
3
26
2
1
Order By: Relevance
“…We found an inversely proportional association between contraceptive use and desire for more children [11]. Previous research has found that maternal grand multiparity is negatively associated with intention to use contraceptives in Nigeria, which indicates that there is unlikely to be a rise in future contraceptive use and a decline in the fertility rates in the near future [12]. Given the importance of religiosity and the how children are viewed within regional social norms, a culturally and religiously sensitive framing of contraception may be necessary.…”
Section: Discussionmentioning
confidence: 68%
“…We found an inversely proportional association between contraceptive use and desire for more children [11]. Previous research has found that maternal grand multiparity is negatively associated with intention to use contraceptives in Nigeria, which indicates that there is unlikely to be a rise in future contraceptive use and a decline in the fertility rates in the near future [12]. Given the importance of religiosity and the how children are viewed within regional social norms, a culturally and religiously sensitive framing of contraception may be necessary.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, research examining determinants of couples' modern contraceptive use has ignored men's crucial role [11,12], which has eventually resulted in underlining the idea of contraceptive use as women's concern, leaving little or no role for men [13][14][15]. It was observed [16] that men, particularly in low socio economic settings, prefer large numbers of children both as a source of labor and profitable gain, and as a source of respect. Men's role as central decision makers, are believed to determine men's and couples' use of contraceptives [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A men's agreement of the use of contraception is a key for effective family planning programs [19,20]. A study illustrated that men had complete decision making supremacy and the ability to result in compliance or submission from their partners [16].…”
Section: Introductionmentioning
confidence: 99%
“…The reason given for the higher PPFP uptake among multiparous women is that when a woman has had a higher number of children, her desire to either space or limit childbearing is usually stronger. 15,19 For the same reason, it has been demonstrated in other studies that couples usually delay contraceptive use until after attaining their desired family size. 15 In this study, this is hinted at by the…”
Section: Discussionmentioning
confidence: 92%